PEMBERDAYAAN MASYARAKT MELALUI PENGELOLAAN BUDIDAYA IKAN LELE SISTEM BIOFOLOK PADA KELOPOK POKDAKAN DI KABUPATEN PINRANG - Damis, Damis; Saenong, Muhammad (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, 2022)
People's low consumption of animal protein needs to be increased by providing a quality and affordable source of protein. Catfish, with intensive system cultivation, can answer 2 such oppositions, a source of quality and cheap protein.. The purpose of community empowerment through the management of catfish farming in the biofloc system is that pokdakan partner groups can apply catfish biofloc technology effectively and efficiently. This service was carried out for three months from July 10, 2020 to August 17, 2020 in Langnga Village, Mattiro Sompe District, Pinrang Regency. This pagabdian uses the sausageization method, discussion and demonstration or simulation. The cultivation of the biofloc system is carried out by growing microbes that will decompose the ammonnia from feces and the rest of the feed which is then useful as a source of natural feed for fish. Analysis of the biofloc system catfish business if carried out on 1 pond with a diameter of 3 meters with a water level of 1 meter with an initial investment of RP 1,350,000 and the cost of producing seeds and feed around IDR 1,780,000, the estimated income and profit of 1 period is around IDR 940,000 or a monthly profit of IDR 313,300. presumably the management of biofok system cultivation can be developed even better